Complete Essential Oils of Laurus Nobilis Inducing Antinociceptive Action by Opioid Mechanism in C-Reflex and Spinal Wind-Up Model in Rat [Aceites Esenciales Totales de Laurus Nobilis Inducen Acción Antinociceptiva Mediante Mecanismo Opioide en el Modelo de Reflejo-C y Wind-Up Espinal en Ratas] - Laurido-Fuenzalida, C; Martinez-Salinas, J; Morales-Munoz, B; Jaimes-Fernandez, L (Universidad de Santiago de Chile, 2020)
The essential oil of Laurus nobilis L. was used to test their antinociceptive efficacy. It was applied intraperitoneally (i.p.) to rats subjected to a nociception test (C reflex and spinal wind-up). The results showed that the essential oil applied at higher doses (0.06 mg/Kg) causes a complete abolition of the spinal wind-up, while the C reflex was unchanged, indicating a clear antinociceptive effect. At lower concentrations (0.012 mg/Kg), there was a lowering in the wind-up by 85% within ten minutes of the essential i.p. oil application. Interestingly, there was an effect of naloxone (0.08 mg/Kg i.p.) When applied, a change occurs that almost entirely reversed the antinociception caused by the essential oil from Laurus nobilis. We conclude that there is a significant antinociceptive effect of the essential oil of Laurus nobilis subjected to electric nociception. In addition, it was observed that naloxone reversed the antinociceptive effect (wind-up) produced by Laurus nobilis. © 2020, Universidad de Santiago de Chile .All rights reserved.